Real interest rates equalization: The case of Malaysia and Singapore - Ling, Tai-Hu; Liew, Venus Khim-Sen; Syed Azizi Wafa, Syed Khalid Wafa (Munich University Library, 2006)
This study provides some evidences showing high degree of financial integration from both evidences of common shocks and real interest parity in the context of two small and open economies, that is, Malaysia and Singapore. Few key policy implications may be suggested from the findings in this study. First, foreign investors who invest in these two countries may need to look for sources of diversification to protect their wealth against the occurrence of contagion effect due to the strong trade and finance relationship between these two countries. Second, the banks and businesses that set rules for interest rates on deposits and loans should be kept consistently with commercial banking practices and key developments in the financial sectors for the betterment of both Malaysia and Singapore economies. Third and most importantly, as two financial markets are highly linked, the monetary and fiscal authorities of both countries should work handin-hand to avoid any potential macroeconomic instability in this region.